Data and scripts for "Experimental evidence on the influence of root-associated fungi on plant growth along altitude" - Burg Skylar; Ovaskainen Otso; Furneaux Brendan; Ivanova Natalia; Abrahamyan Arusyak; Niittynen Pekka; Somervuo Panu; Abrego Nerea (Zenodo, 2023)
These files include the input data and scripts to reproduce the results from the article "Experimental evidence on the influence of root-associated fungi on plant growth along altitude". The fungal OTU and environmental data are stored in the "data_meta_otu.Rdata" file, and the scripts for performing the joint species distribution modelling described in the article are the files "S1-S5". The scripts should be run in the subsequent order from S1 to S5in R software. As extensively explained in the main document, we investigated whether variations in root-associated fungal (RAF) community composition along altitudinal gradients influence plant growth at high altitudes, where both plants and fungi face harsher abiotic conditions. These data correspond toa translocation experiment between pairs of high and low altitude populations of Bistorta vivipara along three arctic altitudinal gradients in Kilpisjärvi. To separate the impact of shifting fungal communities from the overall influence of changing abiotic conditions, we used a root barrier to prevent new colonizations by RAF following translocation. To characterize the RAF communities, we applied DNA barcoding to the root samples using the ITS2 region. Through the utilization of joint species distribution modeling, we assessed the relationship between changes in plant functional traits resulting from experimental treatments and the corresponding changes in the RAF communities.